Doubly charged Higgs through photon-photon collisions in 3-3-1 models - Cieza Montalvo, J. E.; Cortez, Nelson V.; Tonasse, M. D. [UNESP] (American Physical Society (APS), 2008)
We study the production and signatures of doubly charged Higgs bosons (DCHBs) in the process γγ↔H - H++ at the e-e+ International Linear Collider and CERN Linear Collider, where the intermediate photons are given by the Weizsäcker-Willians and laser backscattering distributions. © 2008 The American Physical Society.